Sobre la existencia de una novela policíaca española : un breve repaso a sus principales títulos, autores e hitos - Parra Sánchez, Diego Ernesto (Acta Hispanica, 2015)
This article intends to reflect on theconvenience or inconvenience of talking aboutSpanish detective novel as a solid andinfluential crime novel trend as the British, theFrench or the U. S. crime fiction trends. Withthis aim, apart from having a look to the mainarguments either in favor or against thisconsideration, this work delves into the mostimportant titles and the most representativeauthors, on the one hand, and into the political,social and economical events which havesurrounded the Spanish crime fiction from itsorigin.